Oscillatory Flow Mixer for Pulp Bleaching - Taslim, Taslim; Takriff, Mohd Sabri (ASEAN Journal of Chemical Engineering, 2002)
This paper reports the results of an investigation on the use of oscillatory baffled column as a mixer for pulp bleaching. Unbleached hardwood kraft pulp was bleached using hydrogen peroxide. Variables studied were oscillation frequency, oscillation amplitude, and pulp consistency. The mixing process was achieved by oscillating pulp suspension in a periodically baffled column at a certain frequency and amplitude. The mixing quality of pulp bleaching was quantified using mixing index. The results showed that mixing quality improved with oscillation frequency and amplitude, but decreased with pulp consistency. This typical device is very promising as a mixer for pulp bleaching.